An Analysis of Land Use Succession and Property Value in Ile-Ife, Nigeria - Olusola Oladapo MAKINDE; Olubukunmi Temitope MAKINDE (RIRAI Publisher, 2020)
Land use succession systems have played a crucial role in cities transformation, evading and mitigating the adverse impacts on property value and unplanned development. However, such developments were not aimed at ensuring orderly spatial development which is consistent with land use and sustainable development. This study determined the trends in properties values between the year 2002 and 2016 and examined the relationship between rental values and types of Land Use Succession (LUS) in Ile-Ife, Nigeria. This was to provide information that could enhance property investment decision. Both primary and secondary data were used for the study. Primary data were obtained through the use of the questionnaire. This was administered to landlords, Estate Surveyors and Valuers and on the official of Ife Central Town Planning and Land Services Department. Data were collected from the respondents on the three major roads where LUS was prevalent. Four hundred and fifty buildings were identified out of which 50% were selected. Data collected were analyzed using descriptive and inferential statistics such as trend analysis and Analysis of variance (ANOVA). The result showed that residential properties increased by 42.2% while commercial property increased by 57.8% between the year 2002 and 2016. The result also showed a significant statistical relationship between properties values and types of LUS with corresponding P-values of 0.000, 0.000 and 0.019 for residential-commercial, residential cum commercial and residential-religion types of LUS respectively. The study concluded that an increase in rental value as a result of LUS is capable of enhancing property investment decision.